Use of Tachycardia in Patients With Submassive Pulmonary Emboli to Risk Stratify for Early Initiation of Thrombolytic Therapy: A Case Series Comparing Early Versus Late Thrombolytic Initiation - Jordana Cheta MD; Ashleigh Long MD, PhD; Paul Marik MD (SAGE Publishing, 2017)
Pulmonary embolism (PE) represents a prevalent cause of morbidity and mortality in the United States, with approximately 600 000 cases diagnosed annually. The mortality rate for untreated PE is as high as 30%. Right ventricular (RV) dysfunction is a sign of possible adverse outcomes with right-sided heart failure being the usual cause of death from PE. There is a spectrum of clinical presentations associated with PE diagnoses, from incidental and asymptomatic to rapid hemodynamic collapse. Despite successes in identifying patients with "high-risk" PEs for aggressive thrombolytic interventions and "low-risk" PEs for outpatient anticoagulation, a significant lack of consensus exists regarding intervention modalities for PEs identified as "intermediate risk" or "submassive," defined as normotensive (systolic blood pressure ≥90 mm Hg) with acute RV dysfunction and myocardial injury. In this case series, we review the management and outcomes of 2 patients with submassive PEs and sustained tachycardia in the setting of normal blood pressures, and we address the need to recognize tachycardia as an ominous RV compensatory sign, indicative of impending hemodynamic collapse, that should lead to aggressive therapy with vascular intervention.